Koagulasi Mutu Pendidikan: Ikhtiar Epistemologis Memajukan Lembaga Pendidikan Islam di Indonesia - Majid, Mohamad Arif (Universitas Islam Negeri Mataram, Indonesia, 2024)
Building quality Islamic education institution has been an urgent demand nowadays, particularly with the increase of socio-political, economic, constitutional, and many other state problems which are called by the experts as a multidimension crisis. Hence, the educational sector, in this case is Islamic education institution, is one of the only hopes when other sectors experience crisis. As Islam is a perfect religion, so that an educational institution with the soul of Islam can be eligible to be called as the true Islamic education institution. Such institution, is believed by writer, will be able to solve most problems and demands in this multidimension crisis. The principles, mechanisms, and stages to take the soul of Islam is called as coagulation of education quality. Coagulation is a term in chemistry which could be simply understood as a unique process to purify water by putting a certain coagulant material, while quality is the degree of excellence in a product. Therefore, with this coagulation of education quality, Islamic education institutions are expected to be able to be the value basis for the creations of value dense products needed by other sectors experiencing multidimension crisis which is actually a value crisis. Keywords: coagulation of education quality, epistemological, Islamic education institution Membangun Lembaga Pendidikan Islam yang bermutu adalah suatu kebutuhan mendesak hari ini. Tuntutan akan hal itu semakin terasa urgen saat melihat meningkatnya berbagai problem sosial-politik, problem ekonomi, problem ketata negaraan, dan setumpuk persoalan bangsa lainnya sampai-sampai banyak pakar menyebutnya sebagai krisis multi dimensi. Oleh sebab itu sektor Pendidikan spesifik dalam hal ini lembaga Pendidikan Islam sebenarnya adalah salah satu tumpuan harapan disaat sektor yang lain sedang mengalami krisis. Islam adalah agama yang sempurna, karenanya jika ‘Ruh Islam’berhasil dipakai oleh suatu lembaga Pendidikan maka lembaga Pendidikan tersebut layak disebut sebagai lembaga Pendidikan Islam sejati. Lembaga yang seperti inilah yang diyakini penulis akan mampu menjawab sebagian besar tuntutan zaman yang sedang mengalami krisis multi dimensi ini. Prinsip-prinsip, mekanisme, dan pentahapan dalam ‘pengambilan’ ruh Islam itulah yang penulis sebut dengan istilah “koagulasi mutu”pendidikan. Koagulasi adalah satu istilah dalam ilmu kimia yang secara sederhana bisa dipahami sebagai suatu proses unik dalam penjernihan air dengan memasukkan materi koagulan tertentu. Sementara mutu/ kualitas adalah kelayakan dari suatu produk. Maka dengan koagulasi mutu Pendidikan ini, Lembaga Pendidikan Islam diharapkan benar-benar mampu menjadi basis-nilai bagi lahirnya produk-produk padat-nilai yang dibutuhkan oleh sektor-sektor lain yang sedang mengalami krisis multi dimensi yang sesungguhnya adalah krisis nilai Kata kunci: Koagulasi mutu pendidikan, epistemologis, lembaga pendidikan Islam